Penggunaan Vidio Animasi sebagai Media Edukasi Untuk Mencegah Anemia Pada Kehamilan - Susindra, Yoswenita; Dewi, Riskha Dora Candra; Satya, Malinda Capri Nurul (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
Pregnancy anemia is a global public health issue and this condition contributes to morbidity and mortality rates among women. 42% of pregnant women worldwide experience anemia. In Jember, East Java, the coverage of pregnant women receiving iron supplement tablets is 88.6% of the total pregnant womens. A health knowledge questionnaire given to respondents in the Sumbersari and Kaliwates areas revealed that most respondents' knowledge about pregnancy anemia is still low. A community service activity on "The Use of Animated Videos as an Educational Medium to Prevent Pregnancy Anemia" has shown that this community service activity can improve the knowledge and attitudes of mothers. Most mothers were very enthusiastic about participating in the counseling activities using animated video media because the material presented was relevant to their needs.